Imaging tissues and cells beyond the diffraction limit with structured illumination microscopy and Bayesian image reconstruction - Pospíšil, Jakub; Lukeš, Tomáš; Bendesky, Justin; Fliegel, Karel; Spendier, Kathrin; Hagen, Guy M (GigaScience, 2019)
BACKGROUND: Structured illumination microscopy (SIM) is a family of methods in optical fluorescence microscopy that can achieve both optical sectioning and super-resolution effects. SIM is a valuable method for high-resolution imaging of fixed cells or tissues labeled with conventional fluorophores, as well as for imaging the dynamics of live cells expressing fluorescent protein constructs. In SIM, one acquires a set of images with shifting illumination patterns. This set of images is subsequently treated with image analysis algorithms to produce an image with reduced out-of-focus light (optical sectioning) and/or with improved resolution (super-resolution). FINDINGS: Five complete, freely available SIM datasets are presented including raw and analyzed data. We report methods for image acquisition and analysis using open-source software along with examples of the resulting images when processed with different methods. We processed the data using established optical sectioning SIM and super-resolution SIM methods and with newer Bayesian restoration approaches that we are developing. CONCLUSIONS: Various methods for SIM data acquisition and processing are actively being developed, but complete raw data from SIM experiments are not typically published. Publically available, high-quality raw data with examples of processed results will aid researchers when developing new methods in SIM. Biologists will also find interest in the high-resolution images of animal tissues and cells we acquired. All of the data were processed with SIMToolbox, an open-source and freely available software solution for SIM.
Keywords: zobrazování trojrozměrné; Cell Line; Bayes Theorem; buňky Hep G2; fluorescenční mikroskopie; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Software; algoritmy; králíci; počítačové zpracování obrazu; Animals; lidé; Microscopy, Fluorescence; Humans; zvířata; Hep G2 Cells; Rabbits; Algorithms; buněčné linie; Bayesova věta; software